2022
DOI: 10.1097/prs.0000000000009937
|View full text |Cite
|
Sign up to set email alerts
|

“Spin” in Plastic Surgery Randomized Controlled Trials with Statistically Nonsignificant Primary Outcomes: A Systematic Review

Abstract: Randomized controlled trials (RCTs) are considered the standard when determining the effectiveness of therapeutic interventions. 1 When the goal of an RCT is to show that one intervention or treatment is better than another, it is called a superiority trial. 2 Significant findings would demonstrate that intervention A is better than intervention B and nonsignificant findings could only be interpreted as intervention A not being superior to intervention B. In comparison, a noninferiority trial refers to an RCT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 118 publications
(138 reference statements)
0
2
0
Order By: Relevance
“… 8 Previous investigations of spin in the abstracts of both RCTs and systematic reviews/meta-analyses in plastic surgery have shown a high prevalence of spin. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 Previous investigations of spin in the abstracts of both RCTs and systematic reviews/meta-analyses in plastic surgery have shown a high prevalence of spin. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…8 Previous investigations of spin in the abstracts of both RCTs and systematic reviews/meta-analyses in plastic surgery have shown a high prevalence of spin. 9,10 The primary objective of this study was to determine the prevalence of spin in nonrandomized observational studies about DIEP breast reconstruction. The secondary objectives were to determine the prevalence of each spin category and strategy.…”
mentioning
confidence: 99%